Mini-Review: Mitochondrial dysfunction and chemotherapy-induced neuropathic pain. (24th August 2021) - Doyle, Timothy M.; Salvemini, Daniela
Highlights: Chemotherapies induce mitochondrial dysfunction in peripheral sensory nerves. Mitochondrial dysfunction alters the bioenergetics and nitro-oxidative state. These alterations reduce axonal outgrowth and abnormal sensory neuron activation. As a result, a painful neuropathy emerges for which treatments are limited. Strategies improving mitochondrial function may be useful in treating this pain. Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a somatosensory axonopathy in cancer patients receiving any of a variety of widely-use antitumor agents. CIPN can lead to long-lasting neuropathic pain that limits the dose or length of otherwise life-saving cancer therapy. Accumulating evidence over the last two decades indicates that many chemotherapeutic agents cause mitochondrial injury in the peripheral sensory nerves by disrupting mitochondrial structure and bioenergetics, increasing nitro-oxidative stress and altering mitochondrial transport, fission, fusion and mitophagy. The accumulation of abnormal and dysfunctional mitochondria in sensory neurons are linked to axonal growth defects resulting in the loss of intraepidermal nerve fibers in the hands and feet, increased spontaneous discharge and the sensitization of peripheral sensory neurons that provoke and promote changes in the central nervous system that establish a chronic neuropathic pain state. This has led to the propose mitotoxicity theory of CIPN. Strategies that improve mitochondrial function have shown success in preventing and reversing CIPN in pre-clinical animal models and have begun to show some progress toward translation to the clinic. In this review, we will review the evidence for, the causes and effects of and current strategies to target mitochondrial dysfunction in CIPN.